“Marriage Is Scary” : A Deconstructive Look at Gen-Z’s Perspectives on Marriage (Case Study of #MarriageIsScary Trend on TikTok Platform) - Annisa, Tista Rizki; Asyahidda, Fajar Nugraha; ., Wilodati (Equilibrium: Jurnal Pendidikan, 2025)
The #MarriageIsScary phenomenon, widely discussed on social media, reflects Generation Z's fears and doubts about the institution of marriage. This study aims to reinterpret the meaning of marriage through a deconstructive approach based on Jacques Derrida’s social deconstruction theory, focusing on Gen-Z’s perceptions. Data were collected through documentation of netizens' comments in the form of screenshots responding to the trend on various social media platforms. Thematic analysis was conducted by categorizing data into initial codes, main themes, and sub-themes, visualized in a Sankey diagram. The results indicate that marriage is no longer perceived as the pinnacle of happiness but rather as a space filled with pressure, uncertainty, and burdensome social expectations. This study is further supported by literature reviews discussing Derrida’s social deconstruction theory and shifts in marital values in the context of digital society. The research concludes that Gen-Z’s fear of marriage represents resistance to the dominant normative narratives and idealization of marriage.